Innovation in Liquid Potassium Fertilizer Made from Seawater and Coconut Husk (Cocos nucifera) - Siti Rismariam; M. Yunus; Irwan Irwan (Jurnal Teknologi, 2026)
This study innovates a liquid potassium fertilizer utilizing seawater and coconut coir as sustainable and economical alternatives to inorganic fertilizers. The research aimed to investigate the effects of varying maceration times (4, 8, 12, 16, and 20 days) and coconut coir weights (10, 15, 20, 25, and 30 grams) on the characteristics of the resulting fertilizer, specifically its pH, Total Dissolved Solids (TDS), and K₂O content. The production process involved seawater collection and filtration, followed by coconut coir preparation (soaking, drying, size reduction, and weighing). Maceration was then performed using seawater and varied coconut coir weights over different time periods. The liquid fertilizer underwent pH, TDS, and K₂O analyses. Key findings indicate that pH decreased with increased coir weight and maceration time, ranging from 8.47 to 7.33, remaining safe for plants. TDS increased with longer maceration and higher coir amounts, reaching 6000 ppm after 20 days with 30 grams of coir, signifying enhanced dissolved compound extraction. The highest K₂O content of 0.132% was achieved at 16 days of maceration with 30 grams of coconut coir, indicating optimal potassium dissolution. This suggests that a combination of seawater and coconut coir can produce a liquid potassium fertilizer with promising characteristics, offering an eco-friendly and cost-effective agricultural solution.